2019
DOI: 10.1177/0361198119839340
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Macroscopic Fundamental Diagrams-Based Models with Microscopic Simulations on Real Networks: Importance of Production Hysteresis and Trip Lengths Estimation

Abstract: This work focuses on the application of accumulation-based and trip-based macroscopic fundamental diagrams (MFD) approaches to real transportation networks and discusses the calibration of the MFD shape and trip lengths estimation using a thorough validation of the network dynamics with microsimulation data. This work not only investigates a classical unimodal approach to fit the production MFD, but also a bimodal MFD curve. Different methods of calibrating trip lengths in the reservoir are introduced to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Section 2 was devoted to deterministic arrivals, as is invariably the case in the literature until now, which included a simpler derivation of the model, exact solutions for uniformly-distributed trip lengths, and the characterization of the steady-state. While the variability of trip lengths has an impact on the time to reach steady-state as noted previously Paipuri et al (2019), it was found that under steady-state conditions the accumulation-based model remains valid regardless of the distribution of trip lengths. This is good news because in steady state or in the common case of slowly-varying demand, one may use the accumulation-based model, which is a much more parsimonious model that only requires a good estimation of the average trip length.…”
Section: Discussionsupporting
confidence: 53%
“…Section 2 was devoted to deterministic arrivals, as is invariably the case in the literature until now, which included a simpler derivation of the model, exact solutions for uniformly-distributed trip lengths, and the characterization of the steady-state. While the variability of trip lengths has an impact on the time to reach steady-state as noted previously Paipuri et al (2019), it was found that under steady-state conditions the accumulation-based model remains valid regardless of the distribution of trip lengths. This is good news because in steady state or in the common case of slowly-varying demand, one may use the accumulation-based model, which is a much more parsimonious model that only requires a good estimation of the average trip length.…”
Section: Discussionsupporting
confidence: 53%
“…In this paper, the authors also clearly pinpointed that assuming a single and constant trip length for all vehicles within a network may lead to strong bias with the microscopic simulation results. This was recently corroborated by Paipuri, Leclercq, and Krug (2019). Such an assumption was first conjectured by Daganzo (2007).…”
Section: How Does This Affect the Accuracy Of Mfd-based Simulation?mentioning
confidence: 53%
“…MFD hysteresis loops may appear when congestion does not occur uniformly throughout the network (Buisson and Ladier, 2009). Some studies including Paipuri et al (2019) calibrated MFD simulations using the data of sixth district of Lyon city (Lyon 6), France. They compared unimodal MFD and a bimodal MFD (cars and trucks) and noticed a clockwise hysteresis in the MFD produced from micro-simulations.…”
Section: Background On Road Pricing and Macroscopic Fundamental Diagrammentioning
confidence: 99%